(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Zohrab Tahir always was proud revolutionary past of the people and throughout all the creativity addressed to this important art subject. He trusted in the future of the people because these people passed some revolutions in the history and struggled with enemies for eyelids. In spite of the fact that, he lived in Isfagan, in Tabriz, in Tehran or in Shiraz, it learned itself (himself) as Azeroglu and trusted in that that, dreams of bright future of East people will surely be executed. Zohrab Tahir who was the South Azerbaijani poet in the same degree that in the homeland, we love and in Northern Azerbaijan. In his creativity found the broad display of the page from our revolutionary past, desire of the poet, fight for the free future, and life of Azerbaijan takes the main place. Seeing the awful events which have happened to the Homeland, the poet since young years joined revolutionary movement. From works the feeling of national pride from determination to fight of the people is felt. The people which have seen so many revolutions of South of Azerbaijan, its history and present life were very interesting and clear to the poet.